Merajut Motif Batik Solo Sebagai Solusi Guna Mengatasi Pengangguran Lulusan SMA/SMK di Desa Ngargoyoso Kabupaten Karanganyar Akibat Covid-19 - Dicky Heru Saputra Saputra; Indriyanti Feronika; Sonya Agustina Dewi Rahayu; Alfina Damayanti; Shafira Allayda Hernany Eddy (Abdi Geomedisains, 2022)
Global economic crisis that occurred due in this pandemic, it also triggers various kinds of social problems in wide community. Karanganyar Regency is one of the districts that has felt the impact of the decline in income due to COVID-19. One of them happened in Ngargoyoso Village, Ngargoyoso District. The majority, public of the Ngargoyoso Village graduates from high school/vocational level education, more likely to choose to work. The people of Ngargoyoso Village, who mostly depend on the local agrarian sector, are now experiencing losses due to a decline in several commodities due to the increasing covid-19 outbreak, especially superior commodities (vegetables). Declining incomes, as well as increasing human resources make the need for a forum that can educate the public to develop other potentials that can be done by the community during the pandemic. . Knitting training can be considered to be an effective and efficient activity, because the work is easy and can be done anywhere and anytime. solo batik motif in the training process can also become a characteristic of knitted products from Ngargoyoso Village. In addition, this training can also simultaneously reduce stress levels and depression due to the pressure felt during the pandemic. In the current pandemic era, many teenagers want to do other activities by further developing creativity in their productive age, which can be done at any time